Hubungan School Well-Being dengan Student Engagement pada Siswa SMA di Bukittinggi - Syntia Rahma Dini; Mario Pratama (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Student engagement is an effort to produce changes in the learning environment, both in terms of motivation, behavior, emotional and cognitive. High student engagement can have a positive influence on how to learn and student learning outcomes and can direct students to the goals they want to achieve. This study aims to determine the relationship between school well-being and student engagement in high school students in Bukittinggi. This study used a correlational quantitative approach with 260 subjects, which were determined by simple random sampling technique. The measuring instrument used is Reeve & Tsang's (2011) student engagement scale compiled by Pratama and Guspa (2022) and the school well- being scale is measured using the school well being measuring instrument compiled by Santi (2021).